PSIKOEDUKASI PENGENDALIAN EMOSI PADA PENGGUNA GAME ONLINE DI DESA TELAGA MURNI KABUPATEN BEKASI - Nugroho, Febrian Andi; Nurhidayah, Siti; Supratno, Setyo (DEVOSI, 2022)
The phenomenon of playing online games among the public is an entertainment need that is easily accessible. With the presence of online games, it can be entertaining to get rid of boredom, but it can cause feelings of emotion due to playing online games. This can lead to harsh words or venting emotions to the environment. One way to reduce this is to control emotions. The method used in this activity is psychoeducation for online game users in order to raise awareness to reduce emotions during playing games, especially people in the Telaga Murni Housing RW 08 environment.